Investigating chemical, antioxidant, and sensory properties of chocolate fortified with cactus stems powder - Angor, Malak; Al Khalaileh, Nazieh; Al-Marazeeq, Khaled; Al-Rousan, Walid; Ajo, Radwan (Frontiers in Sustainable Food Systems, 2023)
The present study aims to examine the sensory, antioxidant, and chemical characteristics of chocolate that were enhanced with a powder derived from cactus leaves. Treatments were prepared by fortified chocolate with cactus leaves powder at different levels (0%, 3%, 5%, and 7%) w/w. The results indicate that fortification of chocolate with cactus leaves powder increased significantly (p≤0.05) moisture, protein, ash, total carbohydrate, and fiber of chocolate treatments with cactus leaves powder, in comparison to control group (0%). On the contrary, there was a notable (p≤0.05) reduction in fat content in all the treatments that contained cactus leaf powder. Furthermore, the augmentation of cactus leaves powder in chocolate treatments had a positive impact on their antioxidant activity, which increased with increasing concentration of the powder. In addition, this inclusion of cactus leaves powder aided in lowering the oxidative degradation of the chocolate treatments. The sensory analysis findings revealed no significant difference between mean ratings for overall acceptability of control chocolate and fortified chocolate treatments (p≤0.05).